2008
DOI: 10.1103/physrevlett.101.077001
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Isotope Effects on the Superconducting Transition and Magnetic States Within the Phase Diagram ofY1xPrxBa2Cu3

Abstract: Oxygen isotope (16 O/ 18 O) effects (OIE's) on the superconducting transition (Tc), the spinglass ordering (Tg), and the antiferromagnetic ordering (TN ) temperatures were studied for Y1−xPrxBa2Cu3O 7−δ as a function of Pr content (0.0 ≤ x ≤ 1.0). The OIE on Tc increases with increasing x up to x ≈ 0.55, where superconductivity disappears. For decreasing x the OIE's on TN and Tg increase down to x ≈ 0.7 where antiferromagnetic order and down to x ≈ 0.3 where spin-glass behavior vanish, respectively. The OIE's … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 23 publications
2
62
0
Order By: Relevance
“…5,6 The cuprate high-temperature superconductors (HTS) are characterized by a vanishingly small but positive isotope effect exponent in optimally doped compounds which increases in a monotonic way upon decreasing doping. [7][8][9][10][11][12][13][14] For the optimally doped cuprate HTS the smallest value of the oxygen-isotope exponent α O ≃ 0.02 was obtained for YBa 2 Cu 3 O 7−δ and Bi 2 Sr 2 Ca 2 Cu 3 O 10+δ , while it reaches α O ≃ 0.25 for Bi 2 Sr 1.6 La 0.4 CuO 6+δ . [7][8][9]13,14 In addition, it was demonstrated that in underdoped materials α O exceeds substantially the BCS limit α BCS ≡ 0.5.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…5,6 The cuprate high-temperature superconductors (HTS) are characterized by a vanishingly small but positive isotope effect exponent in optimally doped compounds which increases in a monotonic way upon decreasing doping. [7][8][9][10][11][12][13][14] For the optimally doped cuprate HTS the smallest value of the oxygen-isotope exponent α O ≃ 0.02 was obtained for YBa 2 Cu 3 O 7−δ and Bi 2 Sr 2 Ca 2 Cu 3 O 10+δ , while it reaches α O ≃ 0.25 for Bi 2 Sr 1.6 La 0.4 CuO 6+δ . [7][8][9]13,14 In addition, it was demonstrated that in underdoped materials α O exceeds substantially the BCS limit α BCS ≡ 0.5.…”
mentioning
confidence: 98%
“…[7][8][9][10][11][12][13][14] For the optimally doped cuprate HTS the smallest value of the oxygen-isotope exponent α O ≃ 0.02 was obtained for YBa 2 Cu 3 O 7−δ and Bi 2 Sr 2 Ca 2 Cu 3 O 10+δ , while it reaches α O ≃ 0.25 for Bi 2 Sr 1.6 La 0.4 CuO 6+δ . [7][8][9]13,14 In addition, it was demonstrated that in underdoped materials α O exceeds substantially the BCS limit α BCS ≡ 0.5. 8,10,14 It is important to note here that the values of both, the oxygen and the copper isotope exponents in cuprate HTS are always positive.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The OIE on the transition temperatures of the various phases observed in all cuprate HTS [superconducting (SC), spin-glass (SG), and antiferromagnetic (AFM)] were investigated for the prototype system of cuprates Y 1 − x Pr x Ba 2 Cu 3 O 7 (see Fig. 3) [7]. All transition temperatures T c , T N , and T g exhibit an OIE which is strongest where the respective phase terminates.…”
Section: Isotope Effectsmentioning
confidence: 99%
“…Even though these observations do not necessarily support phonon mediated superconductivity in the classical sense, further isotope effects on other quantities suggest that lattice involvement is essential to the physics of HTS. These are: isotope effects on T * [5,6], the penetration depth λ [2] [7], the average superconducting energy gap [8], with all of them being interrelated and strongly doping dependent in analogy to the one of T c . In addition, local lattice anomalies are present which drive the system into a dynamically inhomogeneous state emerging from charge-rich and charge-poor, but spin-rich, regions [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%